In-vitro validation of MR-based fat quantification at 1.5 T. (25th October 2018) - Linder, N; Rakete, T; Stange, R; Solty, K; Kahn, T; Busse, H
Abstract: Introduction: MRI is an emerging method in obesity research for the quantification of fat content in various body regions. The aim of this study was to determine the accuracy of MR fat-water imaging and MR spectroscopy for fat quantification at 1.5 T in oil-in-water phantoms. Material and Methods: Oil-in-water emulsions were fabricated over the entire range of lipid content (0%–100%). Relative lipid content was then assessed by two-point Dixon MRI, multi-echo Dixon MRI and single-voxel proton MR spectroscopy (SV-MRS) with localization by both stimulated echo acquisition (STEAM) and point-resolved spectroscopy (PRESS). Linear regression and Bland-Altman analyses were used for statistical evaluation of the results. Results: Agreement between MR-derived measures of lipid content and nominal values in phantoms was generally good. Agreement for two-point Dixon was moderate only (R 2 = 0.75) here, especially for lipid contents between 30% and 70%. For multi-echo Dixon, STEAM and PRESS MRS, the coefficients of determination were very high (rounded R 2 = 0.98 for all). Discussion: In conclusion, this work complements previous studies of MR-based fat quantification at 1.5 T and shows that multi-echo Dixon MRI and MR spectroscopy provide close results over the full range of lipid contents.